Expenditure Composition and Distortionary Tax for Equitable Economic Growth - Park, Hyun (IMF Working Papers; Working Paper ;, 2006)
This paper continues the study of optimal fiscal policy in a growing economy by exploring a case in which the government simultaneously provides three main categories of expenditures with distortionary tax finance: public production services, public consumption services, and state-contingent redistributive transfers. The paper shows that in a general equilibrium model with given exogenous fiscal policy, a nonlinear relation exists between the suboptimal longrun growth rate in a competitive economy and distortionary tax rates. When fiscal policy is endogenously chosen at a social optimum, the relation between the rate of growth and tax rates is always negative. These two conclusions suggest that the interaction between fiscal policy and growth may be complicated enough that it cannot be captured in a simple linear model using an aggregate measure of fiscal policy. The sources of nonlinearity include expectation and coordination of fiscal policy, impluse response of government policies, and the presence of positive externality due to government spending.